First World War Poetry Digital Archive - Lee, S; Lindsay, K; Berglund Prytz, Y; Edwards, A (University of Oxford, 2023)
Launched on 11th November 2008 the First World War Poetry Digital Archive (based at the University of Oxford) made available to the general public a wide array of archival resources relating to literature of the First World War. Building on the success of Oxford's 'Wilfred Owen Multimedia Digital Archive', and the 'Virtual Seminars for Teaching Literature' project (1996), this multimedia digital archive contains archival resources from other major British poets of the First World War plus images, text, audio and video of primary contextual materials. The archive was one of 22 projects funded by the JISC Digitisation programme (Apr 2007 - Mar 2009) delivering high quality online content for use by the UK further and higher education communities. Further work was made possible through the JISC Enriching Digital Resources Programme (Oct 2008 - Sept 2009). Please see http://ww1lit.nsms.ox.ac.uk/ww1lit/about and http://ww1lit.nsms.ox.ac.uk/ww1lit/about/documentation for further details.